Anti-CD20 therapy corrects a CD8 regulatory T cell deficit in multiple sclerosis. (December 2021) - Howlett-Prieto, Quentin; Feng, Xuan; Kramer, John F; Kramer, Kevin J; Houston, Timothy W; Reder, Anthony T
Objective: To determine the effect of long-term anti-CD20 B-cell-depleting treatment on regulatory T cell immune subsets that are subnormal in untreated MS patients. Methods: 30 clinically stable MS patients, before and over 38 months of ocrelizumab treatment, were compared to 13 healthy controls, 29 therapy-naïve MS, 9 interferon-β-treated MS, 3 rituximab-treated MS, and 3 rituximab-treated patients with other autoimmune inflammatory diseases. CD8, CD28, CD4, and FOXP3 expression in peripheral blood mononuclear cells was quantitated with flow cytometry. Results: CD8 + CD28 − regulatory cells rose from one-third of healthy control levels before ocrelizumab treatment (2.68% vs 7.98%), normalized by 12 months (13.5%), and rose to 2.4-fold above healthy controls after 18 months of ocrelizumab therapy (19.0%). CD4 + FOXP3 + regulatory cells were lower in MS than in healthy controls (7.98%) and showed slight long-term decreases with ocrelizumab. CD8 + CD28 − and CD4 + FOXP3 + regulatory T cell percentages in IFN-β-treated MS patients were between those of untreated MS and healthy controls. Interpretation: Long-term treatment with ocrelizumab markedly enriches CD8 + CD28 − regulatory T cells and corrects the low levels seen in MS before treatment, while slightly decreasing CD4 + FOXP3+ regulatory T cells. Homeostatic enrichment of regulatory CD8 T cells provides a mechanism, in addition to B cell depletion, for the benefits of anti-CD20 treatment in MS.